La circulation de la pomme de terre : un sujet global pour étudier un processus pluriséculaire d’innovations alimentaires - Williot, Jean-Pierre (Food & History, 2009)
Abstract Known as of 8000 years ago, the potato has become the fourth food-stuff in the world. The diffusion on all continents results from a variety of geographical itineraries. Many different economic actors are implicated in its transformation from a marginal foodstuff to achieve its role as cornerstone in world diets. The potato, source of many easily prepared products, had to first convince consumers that it was also a nutritive food. At present it is one of the most popular products for “fast” cooking. The potato resumes in itself the paradigm of food globalization and is the centerpiece of a remarkable process of agricultural, technical and cooking innovations. The year 2008 was declared “International potato year” by FAO, a sign of the future role it may well play in feeding the world ! Abstract Connue dans les Andes il y a 8000 ans, la pomme de terre est aujourd’hui la quatrième denrée alimentaire dans le monde. Sa diffusion a suivi des trajectoires géographiques multiples. Elle a aussi mobilisé de nombreux acteurs économiques pour passer d’une culture marginale à une base alimentaire essentielle. Source de très nombreux produits préparés faciles d’emploi, il a fallu d’abord convaincre les consommateurs de ses qualités nutritives. Symbole de la globalisation alimentaire, la pomme de terre est au cœur d’un processus remarquable d’innovations agricoles, techniques et culinaires. La FAO lui a dédié l’année 2008 comme un signe de son avenir pour répondre au défi de l’alimentation mondiale.